TEKNOLOGI PENGOLAHAN PUPUK ORGANIK CAIR BERBASIS WHEY KEFIR PADA PERTANIAN CABAI DI NAGARI AMPALU KABUPATEN LIMA PULUH KOTA - Ferawati Ferawati; Erpomen Erpomen; Yuherman Yuherman; Yulianti Fitri Kurnia; El Latifa Sri Suharto (Jurnal Hilirisasi IPTEKS, 2022)
This activity aims to improve the understanding of farmers in making POCs and increase farmer productivity in processing waste into appropriate products for chili farming in Nagari Ampalu, Lareh Sago District, Halaban. Based on identifying the problems that have been carried out, we obtained several things that need to be improved on the chili farming system carried out by farmers. This activity is carried out through counseling and assistance in product manufacture and is equipped with direct implementation on chili farms owned by farmers in Nagari Ampalu. The result of the activity is that farmers who initially only used animal manure without processing have now made changes through this program. Farmer's cattle waste is processed into Liquid Organic Fertilizer (POC) using whey kefir as a source of microbial decomposers. The participation of farmers has resulted in an appropriate product, namely POC kefir, which can be applied directly to chili plants. This product can save the production cost of chili plants. This product can also be continuously produced with basic materials that are easily obtained, most of which are waste. So that the manufacture of this POC does not require high costs. After the implementation on agricultural land gives good results in chili production. POC has the advantage of being able to fertilize the soil because it provides complete nutrients and is easily absorbed by plants. This is what can encourage chili production to continue to increase. Implementing this activity has encouraged the spirit and increased farmers' productivity in processing waste into appropriate products.